1, 2, 3-Triazoles as inhibitors of indoleamine 2, 3-dioxygenase 2 (IDO2). Issue 17 (1st September 2016) - Röhrig, Ute F.; Majjigapu, Somi Reddy; Caldelari, Daniela; Dilek, Nahzli; Reichenbach, Patrick; Ascencao, Kelly; Irving, Melita; Coukos, George; Vogel, Pierre; Zoete, Vincent; Michielin, Olivier
Graphical abstract: Highlights: IDO2 is a potential target in cancer immunotherapy. 4-Aryl-1, 2, 3-triazoles were synthesized and tested in cellular assays for mIDO2 inhibition. Best compound has an IC50 value of 51 μM for mIDO2, twofold selectivity over hIDO1, and is not cytotoxic. Abstract: Indoleamine 2, 3-dioxygenase 2 (IDO2) is a potential therapeutic target for the treatment of diseases that involve immune escape such as cancer. In contrast to IDO1, only a very limited number of inhibitors have been described for IDO2 due to inherent difficulties in expressing and purifying a functionally active, soluble form of the enzyme. Starting from our previously discovered highly efficient 4-aryl-1, 2, 3-triazole IDO1 inhibitor scaffold, we used computational structure-based methods to design inhibitors of IDO2 which we then tested in cellular assays. Our approach yielded low molecular weight inhibitors of IDO2, the most active displaying an IC50 value of 51 μM for mIDO2, and twofold selectivity over hIDO1. These compounds could be useful as molecular probes to investigate the biological role of IDO2, and could inspire the design of new IDO2 inhibitors.